Gray codes and lexicographical combinatorial generation for nonnesting and sparse nonnesting set partitions - Conflitti, Alessandro (2015)
We present combinatorial Gray codes and explicit designs of efficient algorithms for lexicographical combinatorial generation of the sets of nonnesting and sparse nonnesting set partitions of length n.